Evolution of Traditional Outsourcing into Innovative Intelligent Outsourcing - Smartsourcing - Bajec, Patricija (Promet - Traffic&Transportation, 2012)
The concept and practice of traditional outsourcing is certainly not a new concept. Globalisation, competition and other market pressures have driven more businesses to consider using logistics provider to increase efficiency and effectiveness [11]. Many companies have successfully used traditional outsourcing to lower costs and have improved the bottom line. However, unless the company’s efforts are unusually good, true competitive advantage is fleeting when competitors begin outsourcing and achieving similar results [2]. Some companies have discovered even greater returns are possible and are now using advanced form of outsourcing – intelligent outsourcing or smartsourcing, to drive new revenues, quicken time-to-market, and increase innovation [2]. This shift, from traditional outsourcing to intelligent outsourcing - smartsourcing which has become a competitive advantage and is likely over time to become a competitive necessity for all, will be analysed in this paper. KEY WORDS: logistics, growth, globalization, traditional outsourcing, innovation, intelligent outsourcing - smartsourcing